Harnessing Tandem Mass Spectrometry for Rational Medication Use in Pharmaceutical Sciences - Ahmed, Rashed (RADINKA JAYA UTAMA PUBLISHER, 2025)
Tandem mass spectrometry (TMS) has emerged as a critical analytical tool in pharmaceutical sciences, playing a pivotal role in ensuring the rational use of medications. This article explores the applications of TMS across various stages of drug development, quality assurance, and patient care, highlighting its precision and reliability in advancing therapeutic efficacy. TMS facilitates the accurate identification and quantification of drug compounds, ensuring that pharmaceutical products meet high standards of purity and potency. By detecting even trace levels of impurities or contaminants, TMS strengthens the quality control processes critical to patient safety. In the realm of pharmacokinetics and pharmacodynamics, TMS enables detailed monitoring of drug absorption, distribution, metabolism, and excretion (ADME), allowing for a better understanding of drug behavior in the human body. It is also instrumental in therapeutic drug monitoring (TDM), ensuring that medication levels remain within therapeutic windows, thus optimizing dosing regimens and minimizing adverse effects. Additionally, TMS supports personalized medicine approaches by assessing drug interactions and tailoring treatments to individual patients. Through its application in drug discovery, development, and therapeutic monitoring, TMS serves as an indispensable tool for fostering rational medication use, contributing to more effective, safe, and personalized pharmaceutical care.